PSIKOLOGI TOKOH UTAMA DALAM NASKAH DRAMA KERETA KENCANA KARYA EUGENE ICONESCO TERJEMAHAN WS RENDRA - Vidia Aulia; Wika Soviana Devi (Jurnal Komposisi, 2021)
This research was conducted with the aim of describing the psychology of the main character in the drama script "Kereta Kencana" by W.S Rendra such as aspects and structure of his personality. The data in this study is qualitative data based on data narration and description, so that qualitative research is more dominant using interpretative exposure rather than using numbers. The method used in this research is descriptive qualitative research. Qualitative research is a method that pays attention to scientific data, data in relation to the context of its existence. The personality structure of the main characters, namely Grandpa and Grandmother, consists of the id, ego, and superego.